Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ijpo.12539
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and eGFR levels could be linked by the PNPLA3 I148M polymorphism in children with obesity

Abstract: Summary Background PNPLA3 I148M polymorphism has an effect on modulation of estimated glomerular filtration rate (eGFR) in nonobese nondiabetic adults and in children with histologically confirmed nonalcoholic fatty liver disease (NAFLD). Objectives The objective of the study is to explore the impact of PNPLA3 I148M polymorphism on eGFR in children with obesity with and without NAFLD. Methods We genotyped 591 patients with obesity for PNPLA3 I148M polymorphism. Anthropometrical, biochemical, and instrumental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 29 publications
8
45
0
1
Order By: Relevance
“…These findings were also replicated in some cohorts of children and adolescents [28,29], although not in all [30]. For instance, in a sample of nearly 140 overweight children with NAFLD on histology, Targher et al [28], reported that rs738409 G/G genotype was independently associated with both decreasing e-GFR and increasing 24 h urinary protein excretion.…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 88%
See 4 more Smart Citations
“…These findings were also replicated in some cohorts of children and adolescents [28,29], although not in all [30]. For instance, in a sample of nearly 140 overweight children with NAFLD on histology, Targher et al [28], reported that rs738409 G/G genotype was independently associated with both decreasing e-GFR and increasing 24 h urinary protein excretion.…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 88%
“…For instance, in a sample of nearly 140 overweight children with NAFLD on histology, Targher et al [28], reported that rs738409 G/G genotype was independently associated with both decreasing e-GFR and increasing 24 h urinary protein excretion. Another cross-sectional study involving 591 Caucasian children with obesity, it was documented that those with G/G genotype had significantly lower eGFR levels than those with G/C or C/C genotypes [29]. Conversely, in a recent cross-sectional study of 230 Caucasian overweight/obese children, Di Costanzo et al [30], found that children with G/G genotype did not have lower eGFR levels than those with C/G or C/C genotypes.…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 94%
See 3 more Smart Citations